HUMAN GENDER POTENTIAL AND OPPORTUNITIES IN NEW UZBEKISTAN - Dilaram Nugmatullaevna Abdullaeva (Western European Studies, 2024)
This article analyzes the issues of gender empowerment and empowerment of the individual in New Uzbekistan. Gender equality, as one of the important directions of state policy, serves to protect human rights, ensure social justice, and ensure the sustainable development of society. The article highlights the legal framework for gender equality, its role in education and the economy, international cooperation, and measures aimed at eliminating cultural stereotypes. Measures taken to strengthen gender equality contribute to the country's social and economic development.
Keywords: Gender equality; human rights; gender potential; economic opportunities